Highly Symptomatic Progressing Cardiac Paraganglioma With Intracardiac Extension Treated With 177Lu-DOTATATE: A Case Report - Huot Daneault, Alexis; Desaulniers, Mélanie; Beauregard, Jean-Mathieu; Beaulieu, Alexis; Arsenault, Frédéric; April, Geneviève; Turcotte, Éric; Buteau, François-Alexandre (Frontiers in Endocrinology, 2021)
Introduction Primary cardiac paragangliomas are rare tumors. Metastatic disease is even rarer. Surgical management is technically challenging, and sometimes even impossible. Available therapeutic modalities for metastatic disease include external beam radiation therapy as well as systemic treatments, namely 131I-MIBG and more recently, peptide receptor radionuclide therapy (PRRT) with 177Lu-DOTATATE. To our knowledge, this is the first case of progressive unresectable cardiac paraganglioma with intracardiac extension treated with dosimetry based personalized PRRT to be reported. This case is of particular interest since it documents for the first time the efficacy, and especially the safety of the 177Lu-DOTATATE PRRT in this precarious context for which therapeutic options are limited. Case presentation A 47-year-old man with no medical history consulted for rapidly decreasing exercise tolerance. The investigation demonstrated an unresectable progressing metastatic cardiac paraganglioma with intracardiac extension. The patient was treated with personalized 177Lu-DOTATATE PRRT and showed complete symptomatic and partial anatomical responses, with a progression-free survival of 13 months. Conclusions PRRT with 177Lu-DOTATATE should be considered for inoperable cardiac paraganglioma. No major hemodynamic complications were experienced. Therapy resulted in safety and substantially improved quality of life.